Hepatic Involvement and Association with Prognosis in COVID-19 Patients: A Single-Centre Report from Iran - Rabbani, Amirhassan; Baziboroun, Mana; Akbari, Hesam; Pishgahi, Mohamad; Nazari, Sedigheh (Novelty in Biomedicine, 2021)
Background:There were no documents about the non-lung involvement of COVID-19, even in the absence of lung involvement. The present study aimed to report a single-centre experience of liver involvement caused by COVID-19 disease in Iran. MaterialsandMethods:We recorded information of 120 patients who suffered COVID-19 disease, and they were admitted to the intensive care unit at Taleghani hospital in Tehran, Iran, between March and May 2020. Along with clinical and diagnostic parameters, the outcome of patients concerning improvement, disease progression or death was also assessed. Results:In total, 68 patients (56.7%) had abnormal liver dysfunction. The most common changes in liver-related parameters were elevated international normalized ratio (INR) (mean serum level of 2.5) followed by elevated alkaline phosphatase (ALP) (mean serum level of 412 mg/dl). The mean level of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) increased 4 and 9 times more than the standard limit. The overall death rate in COVID-19 patients was 38 patients (55.88%, n=68). Conclusion:Liver injuries are common findings in patients suffering COVID-19 infection and leading to poorer outcomes. Serum bilirubin level of more than 3mg/dl was associated with higher mortality in patients with liver damage.